Studies in Health Technology and Informatics Volume 16 - Health Telematics for Clinical Guidelines and Protocols - Gordon, C. (IOS Press, 2014)
Guidelines and protocols for clinical practice (sometimes also termed practice policies) are receiving increasing attention from clinicians and health services as means for applying best current knowledge to maximise the quality and efficiency of delivered healthcare within the given economic constraints. This volume contains the proceedings of a Conference organized in April 1994 by the Health Telematics programme (1991-1994), the AIM programme, which forms part of the Third Framework Programme for Research and Technological Development of the Commission of the European Communities. Earlier discussions among projects participating in this programme had confirmed the growing and widespread importance of this trend within medicine, and the widely recognised potential for healthcare telematics to facilitate the creation, use and constant improvement of clinical guidelines so as to deliver fullest benefits to patients. This observation was strongly reinforced by the results of the EPISTOL study, an accompanying action of the Health Telematics programme set up to clarify the potential impact of knowledge-based systems (KBS) for the health sector. As the chapter in this volume by Pedro Barahona reports, applications of KBS to the use of clinical guidelines were highlighted by this study as a feasible and worthwhile objective for research and development in health telematics during the next few years.